2018
DOI: 10.1021/acs.cgd.8b00544
|View full text |Cite
|
Sign up to set email alerts
|

Study of SiGe Crystal Growth Interface Processed in Microgravity

Abstract: A Si 1−x Ge x (x ∼ 0.5) crystal measuring 10 mm in diameter was grown by the traveling liquidus zone method using the Gradient Heating Furnace aboard the International Space Station. We quantitatively investigated the composition and shape of the crystal/melt interface during growth by analyzing the grown crystal. The growth interface shapes were obtained by tracing the striations that varied as a result of modulation of the interface near the Si seed to a smooth convex shape as the SiGe crystal growth proceed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…To minimize these adverse e ects of gravity, FZ experiments have also been conducted under microgravity. For instance, it has been shown that the microgravity environment may help minimize the adverse e ect of natural convection and o er quiescent, di usionlimited growth that minimizes undesirable striations (Arai et al, 2018). However, it has been shown that even under microgravity, as predicted, Marangoni convection may induce undesirable growth striations in the grown crystals (Eyer and Leiste, 1985).…”
Section: Introductionmentioning
confidence: 96%
“…To minimize these adverse e ects of gravity, FZ experiments have also been conducted under microgravity. For instance, it has been shown that the microgravity environment may help minimize the adverse e ect of natural convection and o er quiescent, di usionlimited growth that minimizes undesirable striations (Arai et al, 2018). However, it has been shown that even under microgravity, as predicted, Marangoni convection may induce undesirable growth striations in the grown crystals (Eyer and Leiste, 1985).…”
Section: Introductionmentioning
confidence: 96%